Modelos estruturais para a análise de pórticos preenchidos com blocos cerâmicos em edifícios de concreto armado - Montandon, Guilherme Augusto (2018)
The behavior of single-storey, single-bay reinforced concrete infilled frame with masonry panel subjected to static horizontal load was studied using two structural models: i) equivalent strut model (MDE) and ii) model with two-dimensional finite elements for state stress plane (MEF). In the first model, the masonry was replaced by an articulated equivalent diagonal strut, its axial stiffness being defined by the calculation of its width. In the second model, the infilled frame was discretized by two-dimensional finite elements, requiring the simulation of the sliding and separation between the wall surfaces and the reinforced concrete frame. Although equivalent strut models are more attractive for design, the semi-empirical formulas in the bibliography to calculate the equivalent strut width provide very different values. In addition, most of these formulas ignore some parameters that may be important, such as beam flexural stiffness and columns with different sections. For this reason, several numerical analysis with usual geometric and mechanical characteristics will be carried out in single-storey, single-bay reinforced concrete buildings infilled frame with brick blocks panel. The results of the two-dimensional finite element modeling (by software ANSYS) were used as reference for the evaluation of the results provided by the equivalent strut model The measurement of these results allowed to compare them with the analytical expressions for the calculation of the equivalent diagonal width, showing that the Durrani and Luo’s (1994) expression gives more coherent results with the numerical analysis. In addition, a calibration was performed on the expression of Maintone (1974), improving the results provided by it.